1999
DOI: 10.1161/01.str.30.7.1307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stroke Localization on Cardiac Autonomic Balance and Sudden Death

Abstract: Background and Purpose-Stroke has been shown to alter autonomic function. The purpose of this study was to show the differential effects of stroke localization on autonomic function parameters assessed by heart rate variability (HRV). Methods-To determine the differential effect of ischemic stroke localization on autonomic cardiac innervation, we evaluated 62 patients with ischemic stroke and 62 age-and sex-matched controls. The localization of the infarct was determined by CT and MRI. Power spectrum analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
219
3
7

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(242 citation statements)
references
References 29 publications
13
219
3
7
Order By: Relevance
“…In patients with stroke, a disturbance in the autonomic functions caused by the lesion was often described to affect physiological processes in cerebrovascular diseases [38][39][40]. In the context of a decrease in HRV, i.e., SD of RR intervals, we found low frequency and high frequency for patients with stroke [38,40]. In addition, Korpelainen et al showed that skin temperature …”
Section: Influence Of Physical Activity Neurological Deficits and Mmentioning
confidence: 48%
“…In patients with stroke, a disturbance in the autonomic functions caused by the lesion was often described to affect physiological processes in cerebrovascular diseases [38][39][40]. In the context of a decrease in HRV, i.e., SD of RR intervals, we found low frequency and high frequency for patients with stroke [38,40]. In addition, Korpelainen et al showed that skin temperature …”
Section: Influence Of Physical Activity Neurological Deficits and Mmentioning
confidence: 48%
“…Finally, the correlation with ischemic location was not fully investigated. A previous study demonstrated that patients with infarctions involving the insular cortex tended to suffer from autonomic dysfunction, 31 which may influence blood pressure. However, in the present study, few patients had infarctions involving the insular cortex, and the proportion of patients with infarctions involving the insular cortex was similar between the compression and non-compression groups (two in the compression group (13.3%) and five in the non-compression group (12.2%)).…”
Section: Discussionmentioning
confidence: 99%
“…Cнижение ВРС более выраженно при правосторонней локализации церебрально-го поражения. При этом самые низкие значения ВРС регистрировались при вовлечении в патологический очаг правого островка [265]. При пра-восторонней локализации инсульта независимо от поражения островко-вой доли имеется стойкий дефицит вегетативной регуляции, в большей степени за счет парасимпатической составляющей, что может быть свя-зано с более неблагоприятным прогнозом [115].…”
Section: вариабельность ритма сердцаunclassified
“…По данным литературы [36, 114] низкие показатели ВРС выявля-ются при правосторонней локализации церебрального поражения, и в вертебрально-базилярной системе, особенно при поражении правого островка (островка Рейля) [265].…”
Section: вариабельность ритма сердца в зависимости от тяжести и локалunclassified